PERCUTANEOUS NEPHROLITHOTOMY: UPPER VERSUS LOWER POLE CALYX PUNCTURE - Saeed Pansota, Mudassar; Rasool, Mumtaz; Shahzad Saleem, Muhammad; Ali Tabassum, Shafqat (Journal of Postgraduate Medical Institute, 2020)
Objective: To compare the residual stone rate and chest complications of upper versus lower pole calyceal puncture in percutaneous nephrolithotomy (PCNL). Methodology: Four hundred and seventy patients with single stone in the renal pelvis, of either gender were recruited in the study. Patients with multiple stones, staghorn stone, pelvic kidney, calyceal stones and pelviureteric junction obstruction (PUJO) were excluded. Selected patients were divided into two groups randomly i.e. Group A (upper pole calyx) & Group B (lower pole calyx) by using lottery method. Patients remained under indoor care for a minimum of 48 hours after surgery and were evaluated for residual stone and chest complications. Results: Mean age was 33.44 ±7.01 years. Out of 470 patients, 290 (61.70%) were men and 180 (38.30%) were women with men to women ratio of 1.6:1. The residual stone rate was 15.32% for the upper pole PCNL and 26.81% for lower pole PCNL. Chest complication rate was seen in 2.13% and 5.96% for the upper and lower pole PCNL respectively. Conclusions: This study concluded that PCNL through upper pole calyx has better outcome than lower pole calyx PCNL.